Lipoprotein(a) Is the Best Single Marker in Assessing Unstable Angina Pectoris - Vidosava B. Djordjević; Vladan Ćosić; Ivana Stojanović; Slavica Kundalić; Lilika Zvezdanović; Marina Deljanin-Ilić; Predrag Vlahović; Lidija Popović (Cardiology Research and Practice)
This study evaluated whether statin therapy changed a diagnostic validity of lipid and inflammatory markers in ischemic heart disease (IHD) patients. Levels of lipids, lipoproteins, apolipoproteins, inflammatory markers, and atherogenic indexes were determined in 49 apparently healthy men and women, 82 patients having stable angina pectoris (SAP), 80 patients with unstable angina (USAP), and 106 patients with acute ST-elevation myocardial infarction (STEMI) treated or not treated with statins. Diagnostic accuracy of markers was determined by ROC curve analysis. Significantly lower apoA-I in all statin-treated groups and significantly higher apoB in statin-treated STEMI group compared to non-statin-treated groups were observed. CRP showed the best ROC characteristics in the assessment of STEMI patients. Lp(a) is better in the evaluation of SAP and USAP patients, considering that Lp(a) showed the highest area under the curve (AUC). Regarding atherogenic indexes, the highest AUC in SAP group was obtained for TG/apoB and in USAP and STEMI patients for TG/HDL-c. Statins lowered total cholesterol, LDL-c, and TG but fail to normalize apoA-I in patients with IHD.